Structure of Family Groups and Space Use by Steppe Marmots (Marmota bobac): Preliminary Results - Nikol'skii, A.A.; Savchenko, G.A. (Вестник зоологии, 1999)
The structure of family groups on the basis of observation on individually tagged marmots (Marmota bobac Muller) is described. In all 48 captured animals from 11 permanent burrows (including 17 adult females and 26 adult males) were tagged during 1994-1997. Density of families in the biotopes of intensive grazing is 1.9 family/ha. In late summer the home range area of one of the groups under observation was 0.36 ha. In the biotopes of moderate grazing the density is 0.8 family/ha. The home range area of one of the groups during the same observation period was 0.53 ha. In the biotopes of low anthropic influence the population density is less than 0.3 family/ha. The home range area of one of the groups is 0.83 ha. Observations show that in most cases a family group consisted of an adult female with offspring or without it and 2 to 3 adult males. Groups are relatively unstable: during one month observation period there were registered a number of animals' passages from one group to another separated by a rather great distance (more than 300 m). Marmots visit neighbouring home ranges and in some cases move to those become free for some reasons. На основании наблюдения за индивидуально мечеными степными сурками (Marmota bobac Muller) описывается структура семейных групп и использование животными территории. В 1994-1997 гг. было помечено 48 животных, отловленных из 11 постоянных нор, из них 17 взрослых самок и 26 взрослых самцов. Плотность семей в биотопах с интенсивным выпасом составляет 1,9 семьи/га. Площадь участка одной из наблюдаемых здесь групп составляла в конце лета 0,36 га. В биотопах с умеренным выпасом плотность — 0,8 семьи/га. Площадь участка группы в тот же период наблюдений — 0,53 га. В биотопах с низким уровнем антропогенной нагрузки плотность населения сурков — менее 0,3 семьи/га. Площадь семейного участка — 0,83 га. Наблюдения показали, что в большинстве случаев семейная группа состоит из взрослой самки с потомством или без него и 2—3 взрослых самцов. Группы относительно нестабильны: в течение периода наблюдений, равного примерно одному месяцу, регистрировались переходы животных из одной группы в другую на значительные расстояния (более чем 300 м). Сурки посещают соседние семейные участки, а также переселяются на участки, освобождающиеся по той или иной причине.